E-150 Flow-diverter stent for extracranial internal carotid artery reconstruction following dissection: a technical report. (22nd July 2018) - Hilditch, C; Nicholson, P; Brijinkji, W; Agid, R; Krings, T; Pereira, V Mendes
Abstract : Extracranial internal carotid artery (ICA) dissection in an important cause of ischemic stroke in younger adults. The optimal medical and surgical strategies for managing these lesions have not been well established. We report a case series of extracranial ICA reconstruction using overlapping flow-diverter stents for treatment of symptomatic (ICA) dissection presenting with acute ischemic stroke and/or severe hemispheric hypoperfusion. Materials and methods: Consecutive patients undergoing endovascular reconstruction of either occluded or severely narrowed internal carotid arteries due to dissection, and presenting with symptoms of cerebral ischaemia were included. Data were collected on demographic characteristics, antiplatelet management, clinical presentation, imaging findings, treatment characteristics, complications and stroke recurrence rates. Descriptive statistics are reported. Results: Six patients were included. Mean age was 44 years (range 28–60). Five patients were male and one was female. All patients were symptomatic presenting with ipsilateral transient ischemic attacks or stroke. Patients were placed on dual antiplatelet therapy with aspirin and either ticagrelor or clopidogrel prior to the procedure. In cases where patients were not preloaded with dual antiplatelets intravenous Abciximab was used as bridging therapy. Post-stenting angioplasty was performed in all patients. There were no ischemic or hemorrhagic complications. No patients had recurrent ischemic events. Conclusions: ICA reconstruction for extracranial carotid dissection using flow-diverter stents is feasible and can be performed safely. Further studies are needed to confirm our findings as well as the clinical benefit of stenting in this patient cohort. Disclosures: C. Hilditch: None. P. Nicholson: None. W. Brijinkji: None. R. Agid: None. T. Krings: 2; C; Medtronic, Stryker, Cerenovous. V. Mendes Pereira: 2; C; Medtronic, Stryker, Cerenovous.